Alterations in the pulmonary function tests of inflammatory bowel diseases - Ates, Fehmi; Karincaoglu, Melih; Hacievliyagil, Suleyman Savas; Yalniz, Mehmet; Seckin, Yuksel (Aves, 2011)
Background/aims: We aimed to determine the changes in the pulmonary function tests of the patients with inflammatory bowel diseases. Methods: Forty inflammatory bowel dieases patients; 30 ulcerative colitis and 10 Crohn's disease, and age- and sex-matched control group, consisting of 30 healthy persons, were included in the study. Disease activity in patients with ulcerative colitis was assessed by Truelove and Witts Criteria and in Crohn's disease patients by Chron's Disease Activity Index. Results: Pulmonary function tests were found abnormal at least in. one parameter in, 17 / 30 ulcerative colitis patients (56%) and in 5/10 Crohn's disease patients (50%) in the activation period and in 5/30 ulcerative colitis patients (17%) and in 2/10 Crohn's disease patients (20%) in the remission period of the diseases of the same patients. Forced vital capacity, first second, residual volume 1 total lung capacity, diffusing capacity of the lung for carbon monoxide and diffusing capacity of the lung for carbon monoxide per liter alveolar volume values were found significantly impaired in the activation period in comparison with the values of the same patients in the remission period (p<0.01). It was found that pulmonary function test values in patients with inflammatory bowel dieases were not affected by either the type of disease or treatment with 5-aminosalicylic acid. However, they were affected notably by the disease activity. Conclusion: Pulmonary function test abormalities were found frequently in patients with inflammatory bowel dieases without presence of any respiratory symptoms and lung radiograph findings. The severity and frequency of these pulmonary function test abnormalities which were detected even in the remission periods increase with the activation of the disease. Therefore, pulmonary function test may be used as a non-invasive diagnostic procedure in determining the activation of inflammatory bowel dieases and might aid to the early diagnosis of the latent respiratory
Keywords: Inflammatory bowel diseases; pulmonary function tests; carbon monoxide diffusion test